Kontroversi Dasar Hukum Sidang Istimewa MPR dan Maklumat Presiden 23 Juli 2001 (Tinjauan Yuridis Ketatanegaraan) - Nikmatul Huda (Fakultas Hukum Universitas Islam Indonesia, 2001)
A number of controversial policies taken by President Abdurrahman Wahid, for example,concerning the discharge of the head of Indonesian police (Kapoiri), have brought about strong reaction and critic from Legislative Assembly /People's Consultative Council.The conflict bet vifeen two institutions had become worse when President Wahid issued a decree on July 23, 2001 which, eventually, made him loose his power (mandate) in thespecial session of People Consultative Council. The special session or President's policyto fire Kapoiri, if examined from the constitutional law point of view, caused polemic among society, especially in respect to the basis of law employed byeach party.This incidents how edhow vulnerable thes ystem established by constitution is, because some important problems in the constitutional law have not been set up clearly andexplicitly in the constitution. There fore, the constitutional reformationisan urgent agenda which must be finishe das soon as possible.